Pengaruh Usia Terhadap Besarnya Dosis Serap Radiasi Sinar-X yang Diterima Pasien Pemeriksaan Toraks - I Made Hendra Hadinata; I Gusti Ngurah Sutapa (Universitas Hamzanwadi, 2019)
There’s been research aimed at finding out the effects of age on the large absorbed dose of X-ray radiation received by the patient’s thorax examination. The observation data used to figure out the absorbed dose received by the patient is exposure factor consisting of tube voltage (kV), current (A), time (s), and distance (m) of patient from radiation source. The age range of patient obtained in this research is from 17 years until 48 years old, then it’s grouped by the age category set by Depkes. From the observation data of exposure factor and patients age, further do the test using Oneway Anova statistical method test, by taking a significance level of a 0,05. The results from Oneway Anova statistic test is obtained FCalculate value is 1,532 amd sig is 0,211 with FTable value is 2,70 and sig is 0,05 therefore based on test criteria in statistic the early hypothesis (H0) is accepted. Presumably that the age is not affect on the large absorbed dose X-ray radiation received by the patient thorax eximination of range 17 years until 48 years old.